THE SIGNIFICANCE OF MAHMUD KOSHGARI'S HERITAGE IN STUDYING CERTAIN ECONOMIC GEOGRAPHICAL CONCEPTS (Conference Zone, 2022)
This article examines the significance of Mahmud Kashgari's heritage in the study of some economic geographical concepts, including terms such as registon, saylgoh, dilkusho.